INFLUENCE OF Mo AND Nb CONTENT ON THE MECHANICAL AND CORROSION PROPERTIES OF AlCrMoNbZr HIGH-ENTROPY ALLOYS FOR NUCLEAR FUEL CLADDING - Hardiyanti, Heri; Naibaho, Marzuki; Kurniawan, Budhy; Setiawan, Jan; Ginting, Masno; Insani, Andon; Widakdo, Januar (Urania: Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2025)
The effect of varying Mo and Nb content in AlCrMo5%NbZr and AlCrMoNb5%Zr on their mechanical and corrosion properties has been investigated. X-ray diffraction (XRD) analysis revealed the presence of cubic and hexagonal crystal structure, with AlCrMoNb5%Zr exhibiting a higher concentration of hexagonal structures, contributing to improved hardness and corrosion resistance. Scanning electron microscopy (SEM) and energy-dispersive spectroscopy (EDS) confirmed a dendritic morphology with uniform elemental distribution for both samples. Vickers hardness and the corrosion testing shows the AlCrMoNb5%Zr has superior hardness and significantly lower corrosion rate compared to AlCrMo5%NbZr, respectively. These findings suggest that less amount of Nb content enhances mechanical and corrosion properties, making AlCrMoNb5%Zr a potential material for nuclear reactor applications, mainly as fuel cladding material.